Avaliação topológica da estrutura Eletrônica de compostos mesoiônicos - Anjos, Italo Curvelo dos (2017)
The mesoionic compounds comprise a class of heterocycles with wide range of biological and technological applications. Despite many theoretical and experimental studies, some of their properties are still controversial or poorly understood; in particular: charge distribution, the nature of the chemical bonds in the mesoionic ring and the noncovalent interactions in mesoionic complexes. In this work, we sought to clarify these issues through the theoreticalcomputational study of 54 mesoionic compounds and 12 combinations of dimers. Compounds belonging to the 1,3-oxazol-5-one; 1,3-diazole-4-thione and 1,3-thiazole-5-thione rings have been evaluated by a combination of topological methods and charge models. Atomic, bond and ring properties and interactions in mesoionic dimers have been assessed. Results showed that the ring electron density and ring Laplacian were restricted to characteristic range of values for each group studied, which allows us the ring identification using those properties. The bond properties confirmed a prevalance of shared interactions in the mesoionic ring bonds, but with important charge transfers and significant and heterogeous π contribution. When individual atoms were considered, the different charge models exhibited similar qualitative results, but none of them agreed with existing mesoionic definitions. On the other hand, when net charges were considered in rings and fragments, the different models showed large differences and only one of them (QTAIM) agreed with one of the mesoionic definitions. Hence, it is unclear which of the charge models is the most suitable for these compounds. The assessment of mesoionic complexes revealed that interactions in dimers are favored at antiparallel orientations and in the presence of aromatic substituents, that suggests that charge separation and the groups bonded to the ring are paramount in those interactions. Finally, it is concluded that classical mesoionic models do not satisfactorily describe either the charge distribution or the π character of bonds in mesoionic rings.